Topology Optimization of Rear Sprocket of Electric Prototype Vehicle - Winarbawa, Heryoga (Universitas Sanata Dharma, 2025)
Kompetisi Mobil Hemat Energi (KMHE) competes for energy efficient vehicles, which are composed of integrated energy-saving systems. One of the systems that is required to be energy efficient is transmission. The transmission discussed in this study is the sprocket chain transmission system. The rear sprocket is an object that needs to be optimized to obtain a lighter mass, thus efficient in terms of overall weight. Using topology optimization via CAD software, rear sprocket mass can be reduced. The results of topology optimization are used as a reference for changing the shape of the sprocket face, to make it easier in terms of fabrication. These results were then re-tested with static simulations to ensure its strength. The conclusion is that the latest sprocket design has a mass reduction of 66% of its original version and the von Misses stress was only 55% of the yield strength at most.